+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
↳ QTRS
↳ DependencyPairsProof
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
*12(x, minus1(y)) -> MINUS1(*2(x, y))
*12(x, +2(y, z)) -> +12(*2(x, y), *2(x, z))
MINUS1(+2(x, y)) -> MINUS1(y)
*12(x, minus1(y)) -> *12(x, y)
*12(x, +2(y, z)) -> *12(x, z)
MINUS1(+2(x, y)) -> MINUS1(x)
*12(x, +2(y, z)) -> *12(x, y)
MINUS1(+2(x, y)) -> +12(minus1(y), minus1(x))
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
*12(x, minus1(y)) -> MINUS1(*2(x, y))
*12(x, +2(y, z)) -> +12(*2(x, y), *2(x, z))
MINUS1(+2(x, y)) -> MINUS1(y)
*12(x, minus1(y)) -> *12(x, y)
*12(x, +2(y, z)) -> *12(x, z)
MINUS1(+2(x, y)) -> MINUS1(x)
*12(x, +2(y, z)) -> *12(x, y)
MINUS1(+2(x, y)) -> +12(minus1(y), minus1(x))
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDPOrderProof
↳ QDP
MINUS1(+2(x, y)) -> MINUS1(y)
MINUS1(+2(x, y)) -> MINUS1(x)
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
MINUS1(+2(x, y)) -> MINUS1(y)
MINUS1(+2(x, y)) -> MINUS1(x)
POL(+2(x1, x2)) = 1 + x1 + 2·x2
POL(MINUS1(x1)) = 2·x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
↳ QDP
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDPOrderProof
*12(x, minus1(y)) -> *12(x, y)
*12(x, +2(y, z)) -> *12(x, z)
*12(x, +2(y, z)) -> *12(x, y)
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
*12(x, minus1(y)) -> *12(x, y)
Used ordering: Polynomial interpretation [21]:
*12(x, +2(y, z)) -> *12(x, z)
*12(x, +2(y, z)) -> *12(x, y)
POL(*12(x1, x2)) = x2
POL(+2(x1, x2)) = x1 + x2
POL(minus1(x1)) = 1 + 2·x1
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ QDPOrderProof
*12(x, +2(y, z)) -> *12(x, z)
*12(x, +2(y, z)) -> *12(x, y)
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))
The following pairs can be oriented strictly and are deleted.
The remaining pairs can at least be oriented weakly.
*12(x, +2(y, z)) -> *12(x, z)
*12(x, +2(y, z)) -> *12(x, y)
POL(*12(x1, x2)) = 2·x2
POL(+2(x1, x2)) = 1 + x1 + 2·x2
↳ QTRS
↳ DependencyPairsProof
↳ QDP
↳ DependencyGraphProof
↳ AND
↳ QDP
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ QDPOrderProof
↳ QDP
↳ PisEmptyProof
+2(x, 0) -> x
+2(minus1(x), x) -> 0
minus1(0) -> 0
minus1(minus1(x)) -> x
minus1(+2(x, y)) -> +2(minus1(y), minus1(x))
*2(x, 1) -> x
*2(x, 0) -> 0
*2(x, +2(y, z)) -> +2(*2(x, y), *2(x, z))
*2(x, minus1(y)) -> minus1(*2(x, y))